PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI TENAGA KEPENDIDIKAN - Hastuti, Dwi Fuji; Afrinawati, Fitria; Gistituati, Nurhizrah; Rusdinal, Rusdinal; Nellitawati, Nellitawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
In an era of global competition and a commitment to continuous innovation, employee performance is the driving force behind the success of higher education institutions, demonstrating its relevance and widespread impact in meeting the demands of the times. This study aims to describe the influence of transformational leadership on the performance of educational staff at SMAN 3 Padang. Furthermore, this study uses a quantitative descriptive research method through distributing questionnaires to educational staff at SMAN 3 Padang. Based on the data analysis used in the SPSS application, the results of this study are that transformational leadership has a significant influence on improving employee performance. Based on the results of the descriptive analysis, it shows that transformational leadership is in the good category with an average score of 82.67%. In other words, the higher the transformational leadership ability, the better the employee performance will be, and conversely, if employee lack good leadership qualities, their performance cannot be improved and may even worsen. Therefore, based on the above conclusion, it is believed that there is an influence of transformational leadership on employee performance.